Analysis of the Safety Risks of Working With Job Safety Analysis On the Installation of Scaffolding at PT. Jaya Konstruksi Jakarta - Evi Mulyaningsih (Publisher Cv. Inara, 2020)
Scaffolding has a large potential risk of accidents, this is due to more diverse workprocesses and scaffolding installation activities.The purpose to this study was todetermine the level of occupational safety risk in the scaffolding installation process.The method of study is qualitative method. There are 223 people in the studypopulation with the Slovin Formula, we got at least 30 people. The sample used 33people by purposive sampling technique with criteria of worker who have workedfor 3 year working, 1 year scaffolding installation experience and the educationminimize of senior high school. The data collected by deeply interview, documentstudy, observation and questionnaire. Data analyzing by data reduction, datapresentation and conclusion of verification. The results of study shows a. there are80 potential hazard risk identification that can pose a risk hazard; b. theconsequences and probability result is 5 x5, 4 x3, 3x and 2x1; c. the risk assessmentare 37,3 % extreme risk, 30 % high risk, 28.7 % moderate risk and 3.7 % low risk.Scratched risk is 0.038 on housekeeping at the level low risk so can be concludedthat most of scaffolding installation risk are at level extreme and high risk.